Self-directed learning and practice of Italian osteopathic students during summer break: a cross-sectional survey - Giandomenico D'Alessandro; Giacomo Consorti; Francesco Cerritelli (BMC, 2019)
Abstract Background Self-directed learning is a student-centered approach based on the students' evaluation about their own learning needs. Self-directed practice is a component of the self-directed learning which focus on achieving manual and practical skills. Given the abundance of manual skills that students need to develop in the osteopathic curriculum, self-directed practice has become an attractive methodology. Most of the Italian osteopathic educational institutions recognize two types of educational curriculum: T1, for students without a healthcare background; and T2 for students who are already healthcare professionals. The aim of the present study is to investigate the attitudes of Italian osteopathic students toward self-directed practice during the summer break highlighting the possible differences between T1 and T2 students. Methods A web-based closed-ended survey was administered to the students attending one of the Italian osteopathic educational institutions which accepted to participate in the research. Results Two hundred sixty-eight students on 2549 participated to the survey. 64.92% of the students reported to have performed self-directed practice during the summer break. The main difficulty encountered by students in approaching self-directed practice was 'lack of people to exercise with'. Most of the students performed self-directed practice between 1 to 5 h per week. The most common clinical condition encountered was Low Back Pain. The anatomical area most approached was lumbar spine. The most commonly simulated tests were the articular mobility tests. The techniques in which students trained the most were muscle energy techniques. Significant difference was found in self-engagement to the self-directed practice between T1 and T2 students (p = 0.026), and in the reasons to perform self-directed practice (p = 0.027). Conclusions The results of this study could be useful to reveal some aspects of students' academic education and future clinical practice. Therefore this paper can be a useful tool for the institutions to develop strategies to overcome the reported problems students have towards self-directed practice. For example it should be discussed the possibility for the students to observe some senior osteopaths during their practice or to plan to maintain an open tutored didactic environment during the summer break as an extracurricular activity.